Moxifloxacin target site concentrations in patients with pulmonary TB utilizing microdialysis: a clinical pharmacokinetic study. (23rd November 2017) - Heinrichs, M Tobias; Vashakidze, Sergo; Nikolaishvili, Ketino; Sabulua, Irina; Tukvadze, Nestani; Bablishvili, Nino; Gogishvili, Shota; Little, Brent P; Bernheim, Adam; Guarner, Jeannette; Peloquin, Charles A; Blumberg, Henry M; et al.
Abstract: Background: Moxifloxacin is a second-line anti-TB drug that is useful in the treatment of drug-resistant TB. However, little is known about its target site pharmacokinetics. Lower drug concentrations at the infection site (i.e. in severe lung lesions including cavitary lesions) may lead to development and amplification of drug resistance. Improved knowledge regarding tissue penetration of anti-TB drugs will help guide drug development and optimize drug dosing. Methods: Patients with culture-confirmed drug-resistant pulmonary TB scheduled to undergo adjunctive surgical lung resection were enrolled in Tbilisi, Georgia. Five serum samples per patient were collected at different timepoints including at the time of surgical resection (approximately at T max ). Microdialysis was performed in the ex vivo tissue immediately after resection. Non-compartmental analysis was performed and a tissue/serum concentration ratio was calculated. Results: Among the seven patients enrolled, the median moxifloxacin dose given was 7.7 mg/kg, the median age was 25.2 years, 57% were male and the median creatinine clearance was 95.4 mL/min. Most patients (71%) had suboptimal steady-state serum C max (total drug) concentrations. The median free moxifloxacin serum concentration at time of surgical resection was 1.23 μg/mL (range = 0.12–1.80) and the median free lung tissue concentration was 3.37 μg/mL (range = 0.81–5.76). The median free-tissue/free-serum concentration ratio was 3.20 (range = 0.66–28.08). Conclusions: Moxifloxacin showed excellent penetration into diseased lung tissue (including cavitary lesions) among patients with pulmonary TB. Moxifloxacin lung tissue concentrations were higher than those seen in serum. Our findings highlight the importance of moxifloxacin in the treatment of MDR-TB and potentially any patient with pulmonary TB and severe lung lesions.